Case Study of Student Anxiety in Solving Break-Even Point Questions Based on Gender in Indonesia - Ninik Sudarwati; Dies Nurhayati (ILIN Institute, 2019)
Anxiety is an uncomfortable feeling that arises when a person faces problems. This study aims to describe students' anxiety in solving problems based on gender. This research is a qualitative descriptive research with intrinsic case study approach. In this research, the data was collected by video recording, interview and test. Instruments used in this study are video, interview guides, and questions of test. The validity of data was tested by using time triangulation. The subjects were confident when they had solved the problems faced. Subject 2 misunderstood about the basic knowledge and BEP formula, which can be seen from her answers. In solving problems, the subjects forgot about BEP formula, could not concentrate, and were confused in solving the problems faced. The subjects were not confident when they succeeded in solving the problems they faced.